2018
DOI: 10.1016/s1473-3099(18)30597-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple introductions and subsequent transmission of multidrug-resistant Candida auris in the USA: a molecular epidemiological survey

Abstract: Summary Background Transmission of multidrug-resistant Candida auris infection has been reported in the USA. To better understand its emergence and transmission dynamics and to guide clinical and public health responses, we did a molecular epidemiological investigation of C auris cases in the USA. Methods In this molecular epidemiological survey, we used whole-genome sequencing to assess the genetic similarity between isolates collected from patients in ten US states (California, Connecticut, Florida, Illin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
221
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(257 citation statements)
references
References 19 publications
12
221
0
9
Order By: Relevance
“…The phylogenetic data using ITS and D1/D2 regions of the ribosomal genes revealed that the South Asia clade I was the major genotype and the East Asia clade II was a minor genotype of the C. auris outbreak in NY. These results are consistent with whole genome sequencing results reported for NY strains (25). The distinct separation of South and East Asia clades by ribosomal gene sequencing in the present study is encouraging as next generation sequencing technologies are not in widespread use by clinical, public, and commercial laboratories for fungal pathogens.…”
Section: Discussionsupporting
confidence: 92%
“…The phylogenetic data using ITS and D1/D2 regions of the ribosomal genes revealed that the South Asia clade I was the major genotype and the East Asia clade II was a minor genotype of the C. auris outbreak in NY. These results are consistent with whole genome sequencing results reported for NY strains (25). The distinct separation of South and East Asia clades by ribosomal gene sequencing in the present study is encouraging as next generation sequencing technologies are not in widespread use by clinical, public, and commercial laboratories for fungal pathogens.…”
Section: Discussionsupporting
confidence: 92%
“…Initial genomic analysis of the outbreak identified four major genetic groups corresponding to these geographic regions or Clades I, II, III, and IV (8). Clades I, III, and IV are responsible for the ongoing and difficult to control outbreaks in healthcare facilities worldwide (9). Clade II, also termed the East Asia clade, is predominantly associated with cases of ear infection and appears to be less resistant to antifungals than other clades (10).…”
Section: Observationmentioning
confidence: 99%
“…Subsequently, WGS study of C. auris isolates from various hospitals within the USA demonstrated the presence of all four genetically diverse clades suggesting that US patients acquired isolates and or infections from three continents. (18) This spread of C. auris in USA demonstrates that travel and or migration plays an important role in spreading this disease.…”
Section: Introductionmentioning
confidence: 97%